Evropsko pomembne populacije ptic v Sloveniji - Vrezec, Al (Acrocephalus, 2000)
The article discusses bird populations of European significance in Slovenia, due to which Slovenia was listed by The EBCC Atlas of European Breeding Birds among the 10 countries with the highest share in the European popula- tion. There are 15 such species, with a special emphasis put on the Ural Owl Strix uralensis - as the species with the highest important European popula-tion's share in Slovenia (2.1 %), its population density being 1.23 pair/ 100 km2. Among the birds of European significance in Slovenia there prevail thermophilous species (66.7%), while as far as the choice of habitat is concerned, the non-sylvan species (73.3%) are prevalent. The author divided sylvan species into thermophilous (1) and cold-loving (2) species. The non-sylvan species were divided according to their altitudinal distribution into lowland (under 800 m a. - 6 species), upland (above 1,500 m a. - 3 species) and upland-lowland species (inhabiting both altitude belts - 3 species, e.g. Rock Partridge Alectoris graeca). In zoogeographical sense, species with the Mediterranean type of range (93.3%) are prevalent, the special feature of the area being the Alpine-Mediterranean species. Very interesting in its zoogeographical character is the Ural Owl, for it is the only boreal element among the dealt with species and is in Slovenia considereda postglacial relic. The article also presents 93 species with a high share of European population in Slovenia (>=0.2%, the surface proportion between Europe and Slovenia being 0.2%). The author further states 3 reasons for such high share of the European population in such great number of species: (1) great habitat abd ecological diveristy as well as the geographical position of Slovenia (significant for specialised birds - which are in Europe distributed locally - in their selection of habitat, (2) relatively well preserved envionment allegedly rich with food (enables greaterdensities of certain (Abstract truncated at 2000 charac
Keywords: bird; Birds; ptice; ornitologija; Ecosystem; Europe; Slovenia; Slovenija